Desecration, Law and Evil - R. Gaete (Law Text Culture, 2000)
The essential question about the Holocaust "How could this happen?... retains... all its weight, all its stark nakedness, all its horror" (Scholem, in Markle 1995: 149). It is essential because it gathers together all those events that are collectively known as the Holocaust. It expresses both disbelief and a secret hope that if only the horror could be understood it would be less terrifying. The failure to comprehend the organised extermination of a whole people has created a void in History, a hole in the meaningful narratives of History. Such a monstrous event recalls Kant's phrase in Religion within the Limits of Reason Alone (1960: 28): "There is evil". Kant was asserting the existence of substantive, positive evil against the dominant view that 'evil' is no more than a lack: either ignorance or psychological deficiency. Today, even more than in Kant's time, talk of evil may sound naive and as old-fashioned as talking about the sacred. In fact, both are often associated, for example, when talking about violence practised by fundamentalist movements or about Nazi "holy wildness" (Zimermann 1996: 252). One could speak of a 'perverted sacred' akin to that spiritual evil which Schelling called "a pale, bloodless, fanatical spiritualism that despises sensuality and is bent on violently dominating and exploiting it... a perversion of true spirituality" (Zizek 1996: 8).